Карпатський вузол: до проблеми етнокультурного пограниччя (Леопольд фон Захер-Мазох, Станіслав Вінценз) - Барабаш, Ю. (Слово і Час, 2015)
Феномен “карпатського вузла” – австро-польсько-українського літературного
прикордоння репрезентований у статті творчістю Леопольда фон Захер-Мазоха та Станіслава
Вінценза. Народженням, вихованням, долею, творчими інтересами пов'язані з Галичиною-Гуцульщиною, обидва письменники, австрійський і польський, присвятили значну частину
створеного ними (Вінценз – найсуттєвіше з доробку) природі, людям, історії, культурі цього краю. In the paper, the phenomenon of the so called “Carpathian junction”, that is, of Austrian-Polish-Ukrainian literary frontier, is analyzed on the basis of Leopold von Sacher-Masoch’s and Stanisław
Vincenz’s works. Deeply rooted in the culture of Galicia and Hutsul region through their place of birth,
education, biography and the focal points of their writing, the Austrian and the Polish writer depicted
the nature, the population, the history and the culture of this region in many of their texts, which,
especially in case of Vincenz, make out the most important part of their literary heritage. Феномен “карпатского узла” – австро-польско-украинского литературного пограничья представлен в
статье творчеством Леопольда фон Захер-Мазоха и
Станислава Винценза. Рождением, воспитанием, судьбой,
творческими интересами связанные с Галичиной-Гуцульщиной, оба писателя, австрийский и польский,
посвятили значительную часть созданного ими (Винценз –
самое существенное из созданного) природе, людям,
истории, культуре этого края.